Adaptive radiation‐induced epigenetic alterations mitigated by antioxidants - Autumn J. Bernal; Dana C. Dolinoy; Dale Huang; David Skaar; Caren Weinhouse; Randy L. Jirtle (2012)
Humans are exposed to low-dose ionizing radiation (LDIR) from a number of environmental and medical sources.In addition to inducing genetic mutations, there is concern that LDIR may also alter the epigenome.Such heritable effects early in life can either be positively adaptive or result in the enhanced formation of diseases, including cancer, diabetes, and obesity.Herein, we show that LDIR significantly increased DNA methylation at the viable yellow agouti (A vy ) locus in a sex-specific manner (P‫.)400.0؍‬Average DNA methylation was significantly increased in male offspring exposed to doses between 0.7 and 7.6 cGy, with maximum effects at 1.4 and 3.0 cGy (P<0.01).Offspring coat color was concomitantly shifted toward pseudoagouti (P<0.01).Maternal dietary antioxidant supplementation mitigated both the DNA methylation changes and coat color shift in the irradiated offspring.Thus, LDIR exposure during gestation elicits epigenetic alterations that lead to positive adaptive phenotypic changes that are negated with antioxidants, indicating they are mediated in part by oxidative stress.These findings provide evidence that in the isogenic A vy mouse model, epigenetic alterations resulting from LDIR play a role in radiation hormesis, bringing into question the assumption that every dose of radiation is harmful.-Bernal,